Comparative analysis of Salivette® and paraffin gum preparations for establishment of a metaproteomics analysis pipeline for stimulated human saliva. Issue 1 (1st January 2018) - Rabe, Alexander; Gesell Salazar, Manuela; Fuchs, Stephan; Kocher, Thomas; Völker, Uwe
ABSTRACT: The value of saliva as a diagnostic tool can be increased by taxonomic and functional analyses of the microbiota as recently demonstrated. In this proof-of-principle study, we compare two collection methods (Salivette® (SV) and paraffin gum (PG)) for stimulated saliva from five healthy participants and present a workflow including PG preparation which is suitable for metaproteomics.